Enhanced design of electronically reconfigurable integrated microwave filter and antenna for wireless communication systems - Sam, Weng Yik (2018)
The reconfigurable integrated filter and antenna is one of the major interest for researchers due to the potential significant advantages compare to the typical standard integrated structure. The growth in reconfigurable integrating technology is not limited to a single tunable parameter such as operating frequency, bandwidth and attenuation but it can be combination parameters depending on the applications. There are many techniques have been developed to achieve adaptable reconfigurable integrated filter and antenna but majorities of the reconfigurable designs are focused on a single element either on an antenna or the filter. Thus, it limits the tunable range and flexibility response of the reconfigurable design will be a challenging task. On the other hand, developing a Ultra-Wideband (UWB) antenna is one of the crucial components for UWB communications systems and has been widely studied for many years. Moreover, the reconfigurable UWB designs can be developed the desired filtering antenna which can reject unwanted signal interferences. However, most of these techniques produce excessive band rejection, which leads to reject desired frequencies, thus producing a narrowband notch characteristics is a challenging issue. Therefore, the aim of this research is to design novel structure of reconfigurable integrated technique of planar structure which promises a new potential functionality of the microwave devices. Two designs approach were introduced which is reconfigurable SIW filter and antenna and reconfigurable dual band-notched UWB antenna using FR-4 substrate and Roger Duroid RO4350B with dielectric constant of 4.6 and 3.48 respectively. To realize the concept, reconfigurable SIW filter and reconfigurable patch antenna have been combined using the multilayer technique into a single structure while UWB antenna and reconfigurable notch filter were combined on the same planar. To validate the design technique, the equivalent circuit model of the tunable varactor diode network is presented to study the tunability mechanism. Two commercial software programs that have been used in the design and development of two main designs namely Advanced Design System (ADS) software and CST Studio Suite software. All designs were simulated, manufactured and measured. Reconfigurable integrated SIW filter and antenna provide a good attenuation tuning range about 15.5 dB with improvement up to 55 % and only shifts 1 MHz from the origin centre frequency while reconfigurable UWB antenna with band-notched provide a good range up to 210 MHz. This design has smaller compact size of 37.6 mm x 28.0 mm with bandwidth for peak notch of 224.76 MHz and 89.90 MHz for both notches. The experimental results show a good agreement with the simulated results. The benefits of the reconfigurable integrated design are potentially miniaturizing overall structure, good tuning capability, easy to fabricate and cost effective. The outcomes of the proposed reconfigurable integrated design may facilitate improvements in an integrated technique with a good tuning capability for wireless communication systems.